The Influence of Emotional Intelligence and Self-Esteem among Employee towards Organizational Commitment in Public Sector (Global Journal of Management and Business Research, 2014)
Emotional intelligence currently growing attention and earn a spot in the form of psychological studies. Emotional intelligence detected can influence employee commitment in an organization. The theoretical solutions are simply not able to unlock the psychological issues in organizations because it is closely linked to affective, cognitive and human behavior in public sector. In this study, the issues in the workplace are referring to emotional intelligence, self-esteem and commitment of employees. The specific purpose of this study was to test the impact of emotional intelligence among employees whether it able or unable to influence a commitment to the organization through employee self-esteem factor. A total of 196 civil servants in the Local Authority (LA) have been selected as respondents. Measurement tools that are used in the data lump is Emotion Intelligence Self-Description Inventory (EISDI), Rosenberg Self-Esteem Scale (RSES) and the Employee Commitment Survey Revised Version (ECS).The data was then analyzed using hierarchical regression analysis. The findings show that emotional intelligence and four dimensions of emotional intelligence have a direct impact on organizational commitment. In fact, the emotional intelligence and dimensions also has an indirect effect on organizational commitment when self-esteem as mediator factor is controlled. Employee self-esteem later found to function as a partly mediator that affecting the relationship between overall emotional intelligence and four dimensions of emotional intelligence with organizational commitment. The most important findings are found emotional intelligence dimension among employees are able to become more relevant with the increasing availability of commitment of employee when there was the element of self-esteem as a mediator factor.
Keywords: emotional intelligence; self-esteem; organizational commitment; mediator